Gambaran Tingkat Pengetahuan dan Sikap Ibu Hamil Sebelum dan Sesudah Penyuluhan Asi Eksklusif di Wilayah Kerja Puskesmas Wewantara Aceh Utara Tahun 2022 - nabila inong ramadhana, salsa; Mauliza, Mauliza; Yudhi Iqbal, Teuku (Jurnal Ilmiah Manusia Dan Kesehatan, 2024)
Breast milk (ASI) is a specially produced liquid that comes out directly from a mother's breast for baby consumption. Factors related to exclusive breastfeeding are education, work, knowledge, the role of birth attendants and the age of the mother. The percentage of babies who receive exclusive breastfeeding in Aceh Province is 55.4%. North Aceh is still one of the districts that receives low exclusive breastfeeding at 33%. Knowledge and attitudes can be improved through several methods, one of which is the counseling method. The purpose of this study is to determine the picture of the level of knowledge and attitudes of pregnant women before and after exclusive breastfeeding counseling in the Dewantara Health Center area. This research is a quantitative quasi-experimental research with a type of one group pretest-posttest design with 88 respondents, and a simple random sampling technique. The results showed that the majority of respondents' age was 26-35 years old (56.8%), the majority of respondents' education was high school (56.8%), the majority of respondents' pregnancies were multigravida (78.4%), the majority of respondents' knowledge before counseling was sufficient (62.5%) and after counseling in the good category (100%), and the majority of respondents' attitudes before counseling in the sufficient category (48.9%) and after counseling in the good category (100%). The conclusion of this study is that there are differences in knowledge and attitudes of pregnant women before and after exclusive breastfeeding counseling in the Dewantara Health Center area. Counseling has an influence on the knowledge and attitudes of pregnant women in the Dewantara Health Center area. Keyword : breast milk, Knowledge, Attitude, Education.